Assisting the School Principals for Accreditation Site Visit (A Community Service in Pulo Gadung Sub-District East Jakarta) - Supadi S; Evitha Soraya; Easyah Theoline; Salsa Sabillah (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
This community service focuses on providing assistance to school principals on document preparation for the accreditation assessor to review in reference to the standards. This assistance is important for school principals to be reminded about their roles and functions to improve school quality in general and specifically to reflect their efforts in preparing accreditation site visit tools. However, in providing the assistance, the research team focused more on the components of Teacher Quality and School Management. In this community service, the target participants were 50 elementary school teachers in Pulo Gadung District. The design of this community service follows the CBPR design which uses four stages. They are Community Preparation, Community Brainstorming, Community Sorting and Rating; and Community Interpretation (see Fg.1). The CBPR design fully supports collaborative work that is centered or based on a problem that requires a solution. In general, this research design is used with the aim of promoting change or action in society. The research design involved collaborative work between the research team, a representative of the local government and the team of school principal participants.The community service carried out through assisting elementary school principals have emerged mutual benefits among the research team and school principals. The benefits are mutual coordination, communication and cooperation in community orde to improve the quality of education, especially in terms of preparing document for accreditation site visit. Similar activities are a necessity in the future, particularly for schools that have not been involved in the Community Service carried out at this time.